Design and Development of a Website-Based English Learning Platform for Informatics Engineering Students - Diana, Apriana; Antara, Hari Permata; Al Ghfari, Muhammad Zidane (Journey: Journal of English Language and Pedagogy, 2026)
English for Specific Purposes (ESP) is an English language teaching approach designed to address the specific needs of particular disciplines, including Informatics Engineering. This study aimed to design and develop a website-based English learning platform for Informatics Engineering students. The research employed a Research and Development (R&D) method consisting of needs analysis, system design, website development, testing, and evaluation. Data were collected through interviews with students and industry practitioners to identify learning needs and validate the developed platform. The resulting website provides learning materials related to technical vocabulary, reading comprehension, listening exercises, and professional communication in the field of Informatics Engineering. The needs analysis indicated that students required discipline-specific vocabulary, flexible learning access, and interactive feedback to support independent learning. Functional testing confirmed that all major features of the platform operated as intended, while expert evaluation indicated that the learning content was accurate, relevant, and suitable for the target users. The evaluation results demonstrate that the developed platform effectively supports English learning by connecting academic materials with workplace communication needs. Therefore, the website-based learning platform is a feasible supplementary learning medium for improving English competence among Informatics Engineering students and enhancing their readiness for future academic and professional environments.